Models of culture and modelling culture: Visiting artists as cultural ambassadors. (1st March 2014) - Gall, David
However lofty our educational goals, models of culture inform our teaching for better or worse. Therefore the quality of our theories of culture makes a difference to alleviating teacher anxieties about teaching diverse cultures and to better transcultural teaching. Effective preparation for multicultural teaching needs the best models of culture available, opportunities to interact with diverse cultures, and reflective practice about art teaching as a transcultural event. The limitations of dominant models of culture, which generally either assume people are puppets of cultural systems, or that cultural systems are epiphenomena of people's actions, are reviewed. Transformative models developed by Critical Realists are recommended. Reflection on a visiting artist workshop as a case study of transcultural interaction complements the review of theory. Not knowing is the engine of cultural change; and lack of total control a reason for improvisation. Familiarity with culture's Janus faces, fluid/incoherent and comforting/coherent, relieves teacher anxieties.